Letter from Nino Pontini to Gertrude Behr (1969-02-24) - Ponti, Nino (author):::Creator::::::::::::; Behr, Gertrude (recipient)::::::::::::::: (Trieste; Italy, 2023)
Typewritten letter from Nino Ponti to Gertrude Behr, dated 24 February 1969, sent from Trieste, Italy, thanking her for her assistance with the commemoration of A.W. Thayer during the Beethoven bicentennial celebrations in 1970, and mentioning a memorial stone that was to be placed at Thayer's home in Trieste.